Appreciation of food safety practices based on level of experience - Brannon, Laura A.; Pilling, Valerie K.; Roberts, Kevin R.; Shanklin, Carol W.; Howells, Amber D. (My University, 2009)
This study sought to determine if no experience, basic experience, or well-informed experience (defined as basic experience and formal food safety training) in a foodservice operation would influence attitudes, subjective norms, and perceived behavioral control toward three important behaviors that can help prevent foodborne illness (handwashing, using thermometers, and sanitizing work surfaces). Results suggest that formal training increases respondents’ appreciation of the importance of these food safety practices. Those with formal food safety training identified more attitude, subjective norm, and perceived behavioral control constructs than participants with basic experience or no experience in foodservice. Factors that help and impede employees in following proper food safety practices were identified. Foodservice operators and sanitarians can utilize these results to employ strategies to address the barriers preventing employees from applying food safety practices and to increase compliance with food safety regulations during individual inspections within operations, respectively.
Keywords: Food safety; Behaviors; Experience; Restaurants; Employees; Theory of planned behavior